Evaluating the Gifted Students’ Understanding Related to Plasma State Using Plasma Experimental System and Two-Tier Diagnostic Test - Saadet Deniz Korkmaz; Bahadir Ayas; Eren Can Aybek; Suat Pat (Journal of Education in Science, Environment and Health)
The purpose of this study was to investigate the effectiveness of the experimental system design related to plasma state on the gifted students’ understanding on the subject of the plasma state. To test the research hypothesis, one group pretest-posttest research model was carried out with 18 eighth-grade (4 girls and 14 boys) gifted students in mathematics and science, attending to a university-based after school program for gifted students. A two-tier achievement test (Plasma Achievement Test-PAT) consisting of 10 items used as a pretest and posttest. First tier of the test consists of multiple-choice items and the second tier consists of open-ended items. Students were asked to find the correct answer in the first tier and write the reasons (justifications) for their answers in the second tier. Pretest and posttest mean scores of first and second tier scores were compared with statistical analyzes. Also the students’ justifications for the second tier of the test was used to make content analyzes. From pretest to posttest an increase was found in open-ended tier scores. The difference between pretest and posttest wasn’t statistically significant for multiple-choice tier scores. From the findings it can be concluded that the experiment system was effective on the gifted middle school students’ understanding on the subject of the plasma state.